PROBLEM BULLYING DAN USAHA GURU BIMBINGAN DAN KONSELING UNTUK MENANGGULANGINYA - Erlindawati Erlindawati; Irman Irman (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Bullying is behavior consciously carried out by a person to harass and hurt another person. Ideally, guidance and counseling teachers (BK teachers) are required to pay attention to preventing bullying behavior, The purpose to be achieved in this study is to describe the understanding of how the role of guidance and counseling teachers in overcoming bullying problems among students. It can be seen from the implementation program of guidance and counseling teachers in overcoming bullying and how the results have been achieved by the efforts of guidance and counseling teachers in overcoming bullying behavior. The method used in this study is qualitative descriptive method. The data collection technique used is interviews. The population of this study was all BK teachers of State High School in Pasaman Regency, The sample of this study included high school counseling guidance teachers throughout Pasaman Regency using purposive sampling techniques with 15 BK teachers. The results of the interview about BK teachers' efforts to overcome bullying behavior from the questions given to guidance and counseling teachers on average answered that the problem of bullying in every school exists. Guidance and counseling teachers already have a program for implementing counseling guidance from student need assessments that describe the content of the program one about bullying, so from this result BK teachers contain in overcoming the problem of bullying in classical services, individual counseling services, group guidance services, and group counseling so that the problem of bullying increases and teachers some BK teachers are involved in anti-bullying school programs making it easier for teachers Guidance and Counseling in implementing the program, as well as BK teachers also conducting mediation services in resolving the case.